Nonperforming Loans in Sub-Saharan Africa : Causal Analysis and Macroeconomic Implications - Fofack, Hippolyte L. (World Bank, Washington, DC, 2012)
This paper investigates the leading causes of nonperforming loans during the economic and banking crises that affected a large number of countries in Sub-Saharan Africa in the 1990s. Empirical analysis shows a dramatic increase in these loans and extremely high credit risk, with significant differences between the CFA and non-CFA countries, and substantially higher financial costs for the latter sub-panel of countries. The results also highlight a strong causality between these loans and economic growth, real exchange rate appreciation, the real interest rate, net interest margins, and interbank loans consistent with the causality and econometric analysis, which reveal the significance of macroeconomic and microeconomic factors. The dramatic increase in these loans is largely driven by macroeconomic volatility and reflects the vulnerability of undiversified African economies, which remain heavily exposed to external shocks. Simulated results show that macroeconomic stability and economic growth are associated with a declining level of nonperforming loans; whereas adverse macroeconomic shocks coupled with higher cost of capital and lower interest margins are associated with a rising scope of nonperforming loans. These results are supported by long-term estimates of nonperforming loans derived from pseudo panel-based prediction models.